Pembangunan Ruang Terbuka Hijau Melalui Budidaya Tanaman Secara Vertikultur Di Kawasan Perkotaan Kelurahan Wonorejo Kecamatan Tegalsari Kota Surabaya - Anasthasia Marshanda; Dewi Ratih; U'ud Uda Marlina; Moch. Raihan Ramadhani; Nurul Azizah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Surabaya is the second largest metropolitan city in Indonesia, meaning that population growth is relatively dense. So that in Surabaya many vacant land functions are converted into residential land and public buildings. This has become a problem, especially in terms of the environment, which makes reforestation difficult. Urban Agriculture or Urban Farming is a method of growing crops in urban areas with relatively narrow land. One example of Urban Farming that is rife in Indonesia is verticulture. Verticulture is the cultivation of plants carried out vertically or stratified. Utilization of the walls of residents' houses through used bottle media verticulture can be used as an alternative to plant cultivation in limited land conditions. This system is able to solve the problem of reforestation, especially in the Wonorejo area. An indication of the success of this work program is the enthusiasm of the residents and the benefits in terms of aesthetics, health, and economy.